Interrogating vitality of the streets in two cypriot towns / Siavash Jalaladdini and Derya Oktay - Oktay, Derya (Faculty of Architecture, Planning and Surveying, 2013)
This paper focuses on the issue of vitality in urban public spaces, streets in particular, as a major indicator of their success and as one of the determinants of liveable cities. The study first provides a theoretical framework for understanding the social value and role of urban public spaces in quality of urban life. Second, it discusses essential components of vitality in streets. Finally, it investigates vitality and its determinants in two main streets in Famagusta and Kyrenia, in North Cyprus. The paper highlights some issues such as proper connection and proximity to important magnets, along with physical and social attributes in the street area.